2D Materials: Enriched Fluorescence Emission from WS2 Monoflake Empowered by Au Nanoexplorers (Advanced Optical Materials 14/2017). Issue 14 (17th July 2017) - Sow, Belle Miaoer; Lu, Junpeng; Liu, Hongwei; Goh, Kuan Eng Johnson; Sow, Chorng Haur
Abstract : Au nanoparticles (NPs), presented by Chorng Haur Sow and co‐workers in article number1700156, behave like nanoexplorers that map out subtle and hidden chemical heterogeneity within the tungsten disulfide (WS2 ) monoflake by way of site‐selective decoration on the WS2 monoflake. The resultant decorated Au NPs patterns trace the concentric fluorescence pattern found on the WS2 monoflake. The Au NPs enhance the fluorescence intensity in selected regions within the WS2 monoflake.